Not one less, beyond the protest march, the field of dispute - Muñoz Cabrejo, Fanni (2019)
The article sets out to study the Ni Una Menos Perú 2016 movement with the objectives of identifying and analyzing the game of tensions and negotiations between the several feminist collectives that participated in the August 13, 2016 march. This march presents different ways of carrying out politics between new collectives and established feminist organizations in a context of global relations, social networks, and within the authoritarian Peruvian society. This interaction also reveal the intersection between gender and race, class, and ethnicity. The study seeks to address how a movement that became a platform for thousands of women who brave to narrate violence accounts to which they were subjects, become fragmented. The study consists of seven in-depth interviews to members of the most active and diverse collectives.